Relationship of Perceived Social Support With the Activities of Daily Living in Older Adults Living in Rural Communities in Iran - Fatemeh Jokar; Abdol Rahim Asadollahi; Mohammad Hossein Kaveh; Leila Ghahramani; Mahin Nazari (University of Social Welfare & Rehabilitation Sciences, 2020)
Objectives: The increasing trend in aging population raises the need to pay attention to the daily activities of the elderly and their social support as an effective factor in promoting their health. This study aims to investigate the correlation of perceived social support and demographic variables with the Activities of Daily Living (ADL) in older adults living in rural communities in Iran. Methods & Materials: This is a descriptive-analytical study with cross-sectional design conducted on 430 elderly people aged ≥60 years living in a rural community in Iran (Bayza county located 45 km away from Shiraz city) who were selected using  a convenience sampling method. Procidano & Heller's Perceived Social Support - Family Scale (PSS-Fa) and the ADL scale for the elderly were used for data collection. The ADL questionnaire's internal consistency by calculating Cronbach's alpha coefficient was obtained 0.96. The PSS-Fa with a Cronbach's alpha coefficient ranging from 0.88 to 0.91 has acceptable internal consistency. The reliability of its Persian version using Cronbach's alpha coefficient was obtained 87%. Data were analyzed in SPSS V. 25 software using multivariate ANOVA and regression analysis. Results: The mean±SD age of the participants was 69.67±7.067 years. The mean score of PSS-Fa and the ADL scale was reported 16.55± 5.16 and 55.10±3.07, respectively. Perceived social support, education and age had significant effect correlation with the ability to perform ADL in the elderly (P<0.001), while marital status and gender showed no significant correlation (P>0.05). The age factor was inversely correlated with the ability to perform ADL; hence, the independence of older adults decreases with the increase of age. Conclusion: Many demographic variables and social support affect the ability to perform ADL in the elderly. Social support can be used as a social investment to improve the quality of life of the elderly. Therefore, considering that one of the duties of health care providers is to improve the health status of the elderly, it is necessary for health care providers to increase social support and maintain and promote a healthy and active life for them through educational programs and periodic physical examinations.